2016
DOI: 10.1080/15384101.2016.1189043
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of Sun4p and its interaction with proteins in the yeast birth scar

Abstract: Yeast harbor several proteins with predicted glucanase activity that are potentially involved in cell wall remodeling during different processes, including mitosis. Here, we showed that 2 of these putative glucanases, Sun4p and Dse2p, co-localize to the yeast birth scar, dependently on presence of the third glucanase, Egt2p. The absence of these glucanases results in inefficient mother-daughter cell separation. The Sun4p, Dse2p and Egt2p localize to the daughter side of the bud neck, possibly forming a complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We focused our search on homologues of SUN4; SUN4 and SIM1 are post-whole genome duplication paralogues, as are UTH1 and NCA3 ( 72 ). These putative glucanases are secreted proteins that localize to the bud scar in S. cerevisiae ( 73 , 74 ). We analysed transcript annotations of SUN4 homologues from other ascomycete fungi C. albicans , N. crassa , A. fumigatus and S. pombe .…”
Section: Resultsmentioning
confidence: 99%
“…We focused our search on homologues of SUN4; SUN4 and SIM1 are post-whole genome duplication paralogues, as are UTH1 and NCA3 ( 72 ). These putative glucanases are secreted proteins that localize to the bud scar in S. cerevisiae ( 73 , 74 ). We analysed transcript annotations of SUN4 homologues from other ascomycete fungi C. albicans , N. crassa , A. fumigatus and S. pombe .…”
Section: Resultsmentioning
confidence: 99%
“…We focused our search on homologues of SUN4; SUN4 and SIM1 are post-whole genome duplication paralogues, as are UTH1 and NCA3 (Byrne and Wolfe 2005). These putative glucanases are secreted proteins that localise to the bud scar in S. cerevisiae (Kuznetsov et al 2013; Kuznetsov, Vachova, and Palkova 2016). We analysed transcript annotations of SUN4 homologues from other ascomycete fungi Candida albicans, Neurospora crassa, Aspergillus fumigatus , and S. pombe .…”
Section: Resultsmentioning
confidence: 99%
“…Other cluster V member genes ( EGT2 and SUN4 ) have also been reported to encode glycosidases, and our results clearly showed that genetic perturbation prevented efficient daughter cell separation in all cluster V mutants. Consistent with the mutant phenotypes, co-localization studies have revealed that Dse2, Egt2, and Sun4 form a complex at the birth scar [ 51 ]. Cluster V mutants exhibited no defects in cell-cycle progression or daughter cell growth in the next cell cycle, indicating lesser effects of these genes in cell proliferation.…”
Section: Discussionmentioning
confidence: 87%